Understanding the effects of individual attitudes and residential neighborhood types on university commuters’ bicycling decisions - Park, Yujin; Akar, Gulsah (Journal of Transport and Land Use, 2019)
This study investigates the effects of individual perceptions and residential neighborhoods on university commuters’ bicycling decisions using the 2015 Ohio State University Travel Pattern Survey data. We generate eight attitudinal/perceptual components based on the 26 bicycling-related questions that capture detailed perceptions of commuters toward bicycling, neighborhood environments, and residential location choice. We create distinct neighborhood typologies combining land use and socioeconomic characteristics, including population, employment, housing and intersection densities, housing types, median age of housing stock, and median household income. Probit regression models are estimated to assess the effects of sociodemographic, attitudinal/perceptual components and neighborhood types while accounting for the residential self-selection effect. Results show that people residing in different neighborhood types reveal significant attitudinal differences in terms of their conditional willingness to bicycle, and evaluation of bicycle friendliness of neighborhoods and routes. We find that bicyclists are more likely to live in neighborhoods that they perceive as having good-quality for bicycling in terms of access to bicycle facilities and lower traffic levels. Results also show the significant association of neighborhood types with bicycle commuting outcomes. People from medium-density, mixed-use, and suburban single-family neighborhoods are less likely to commute by bicycle as compared to those from high-density, mixed-use neighborhoods.